MOBILE ASSISTED LANGUAGE LEARNING: WHAT'S UP WITH WHATSAPP - Eny Dwi Marcela (English Department, STKIP PGRI Bandar Lampung, 2020)
Mobile phones are viewed as significant aids to English language learning. Numerous studies have been conducted in different contexts on mobile assisted language learning (MALL) that indicate the benefits of mobile devices for English language learning. During the recent technological years, language learning has been attempted to transform its path from the conventional methods to instrumental applications. Mobile phone provides people to reach and exchange information through chats (WhatsApp). With the rapid increase in the use of mobile devices nowadays, especially smartphones, it is only natural for educators to turn to mobile technology to examine how it can be fully integrated in an educational context to support students’ learning beyond the classroom. This study attempts to solve the lack of communicative learning opportunities by introducing mobile-assisted language learning with Whatsapp. In addition, it tries to investigates the perceptions of students towards the use of Whatsapp as a tool for develop their English writing skill. To achieve the result, a sample of 50 sophomores from the Department of English Education of STKIP PGRI Bandar Lampung, aged 18 to 20 years old. The results suggest that mobile-assisted language learning helps to create language immersion, which effectively motivates the learners further. Therefore, mobile-assisted language learning is promising in English learning for college students.